Ashita no Joe. Fighting for tomorrow. 1 - Takamori, Asao, 1936-1987 (Kodansha USA Publishing, LLC, 2024)
A young drifter named Joe Yabuki wanders through the slums of Tokyo, but when the local ruffians try to give him a hard time he teaches them a rough lesson with his fists. The spectacle sparks a gleam in the eye of an old drunk who happens to be watching - Danpei Tange, a failed boxer and former coach who sees something special in the boy. He pleads with Joe to train with him off, but the cocky young fighter brushes him. Later, though, when Joe is arrested and put in a juvenile detention facility, he realizes that he's going to need to hone his raw fighting skills if he wants to survive. Thus is born a partnership that might just take Joe all the way to the top...